2021
DOI: 10.1111/1756-185x.14227
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic myocardial dysfunction was revealed by feature tracking cardiac magnetic resonance imaging in patients with primary Sjögren’s syndrome

Abstract: Aim To evaluate subclinical left ventricular (LV) regional dysfunction in patients with primary Sjögren's syndrome (pSS) using feature tracking cardiac magnetic resonance (FT‐CMR) imaging and to identify pSS characteristics independently associated with LV regional dysfunction. Method Fifty patients with pSS and 20 controls without cardiovascular disease underwent non‐contrast CMR imaging. Labial gland biopsy was performed in 42 patients (84%). Disease activity was assessed using the European League Against Rh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Hypertension and COPD appear more prevalent in the PDF group whereas peripheral vascular disease and infections are more prevalent in the HSB group, amongst others. Several studies have identified that PSS patients have a higher risk for cardiovascular disease ( 8 10 , 20 ), it is possible that these patients are more likely to be in the HSB group. The comorbidities associated with the LSB and DDF groups appear to be more limited.…”
Section: Discussionmentioning
confidence: 99%
“…Hypertension and COPD appear more prevalent in the PDF group whereas peripheral vascular disease and infections are more prevalent in the HSB group, amongst others. Several studies have identified that PSS patients have a higher risk for cardiovascular disease ( 8 10 , 20 ), it is possible that these patients are more likely to be in the HSB group. The comorbidities associated with the LSB and DDF groups appear to be more limited.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it was also reported that myocardial injury is typically clinically silent in patients with RA, and this could explain the lack of data on cardiac events in patients with SS, since clinical and pathophysiological characteristics are often shared between RA and SS. In recent papers, it was a high prevalence of myocardial fibrosis in the patients with SS who underwent to cardiac magnetic resonance imaging (cMRI) was observed, which can be used to obtain a quantitative functional evaluation of the myocardium [ 42 , 43 ]. In these studies, emerging data highlight that lymphocytic infiltration into the myocardium is conceivable as a pathological characteristic of myocardial fibrosis in SS patients.…”
Section: Clinical Fibrotic Manifestation In Ssmentioning
confidence: 99%
“…In fact, myocardial fibrosis is present in patients with SS without cardiac symptoms, and alterations in cMRI data were often linked with SG focus score (FS) ≥ 3 [ 42 , 44 ]. This study suggests a significant association between myocardial fibrosis and the degree of lymphocytic infiltration into the SGs as an important prognosis factor for SS [ 43 ]. Yokoe et al, in an interesting study, have obtained several important results from the observation of a representative number of SS patients by the use of non-contrast cMRI, without cardiovascular clinical symptoms [ 43 ].…”
Section: Clinical Fibrotic Manifestation In Ssmentioning
confidence: 99%
See 2 more Smart Citations